PENGARUH CR, ROA DAN EPS TERHADAP NILAI PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI - Karin Karin; Hendang Tanusdjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research was conducted with the aim of knowing the effect of Current Ratio (CR), Return on Assets (ROA) and Earning per Share (EPS) on company value in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. The sample was selected by using purposive sampling method and the amount of data that met these criteria was 12 companies. The data processing technique in this study uses multiple regression analysis with the help of the SPSS (Statistical Product and Service Solution) program for Windows version 25 and Microsoft Excel 2010. The results of this study indicate that the ROA variable has a significant effect on firm value.Meanwhile, the variavels of CR and EPS have no significant effect on firm value.Simultaneously CR, ROA and EPS have a significant effect on firm value. The implication of this research is the need for the role of company management in increasing financial ratios in order to increase company value so that it can attract investors.